Optical and structural properties of composites films based on Ce3+‐doped yttrium aluminium garnet nanoparticles embedded in polystyrene. (26th May 2022) - Hamroun, Mohammed Salah Eddine; Bachari, Khaldoun; Mechernene, Lahcene; Guerbous, Lakhdar; Chebout, Redouane; Guenanou, Ahmed; Boukerika, Allaoua
Abstract: In the present work, attempts have been made to prepare scintillating nanoparticle composite films of Ce 3+ ‐doped Y3 Al5 O12 (YAG:Ce) embedded in a polystyrene (PS) polymer. A YAG:Ce phosphor has been previously synthesized using the sol–gel method. YAG:Ce‐PS composite films of 250 ± 30 μm thickness were prepared using a solvent casting procedure with different PS/solvent concentration and a different mass ratio between nanoparticles of YAG:Ce and PS. X‐ray diffraction analysis confirmed that the YAG:Ce powders were successfully prepared. Using thermogravimetric analyses and differential scanning calorimetry, we found that the glass transition temperature (Tg) and thermal degradation were shifted to higher temperatures for composite films relative to pure PS. Photoluminescence showed the yellow emission of the Ce 3+ ‐doped YAG phosphors, which was attributed to the 5 d→ 4 f transition of Ce 3+ ion and the intensity of the emissions changed with the mass ratio of the YAG:Ce nanoparticles incorporated in the polymer and with the concentration of the polymer solution. Abstract : Thin films composite were prepared using polystyrene and Y3 Al5 O12 :Ce 3+ nanophosphors. Polystyrene polymer encouraged us to select it as a candidate due to its high impact resistance, ease of fabrication, flexibility, transparency, and cost‐effective technologies. By varying the mass ratio and the concentration of the polymer solution, we tried to find the best parameters to develop the scintillator composite with better light and good physical properties without losing the transparency and homogeneous distribution of the nanoparticles in polymer matrices.